Gender violence in the university and the UNLPam intervention protocol (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Violence as a form of discrimination and, consequently, as a violation of the minimum foundational principles of the global legal and ethical order were very recently considered a problem in higher education institutions.In order to be able to analyze violence in the framework of universities, as a serious impact on the right to life without violence, to education and to work, this article is organized as follows: in the first section we address the feminization of the higher education, especially in law courses; secondly, we walk through the basic conceptualization of gender violence according to current regulations and the problem of institutionalizing the gender perspective.A third section makes a brief comment on the protocol of the National University of La Pampa (hereinafter UNLPam); Fourth, we analyze the opinions of Legal Sociology students from the Law School of the Faculty of Economic and Legal Sciences of the UNLPam collected in the surveys carried out in 2020 and 2021 and, finally, we close with a few words of reflection.
Keywords: violence protocols; gender perspective; higher education